Independent advice circular in corporate exercises: revisiting the law on fairness opinion - Ambaras Khan, Mushera Bibi; Hamdan, Nur Nadiah; Ab Jabbar, Nurhafiza (IIUM Press, 2014)
Independent advice circulars are required in a broad range of corporate transactions. The advice circulars are extensively used in takeovers and mergers of companies. The board of directors of the target company is required to appoint an independent adviser to prepare the independent advice circular, in order to assist the shareholders of the target company in making their decision in relation to the takeover offer. Malaysia has taken an approach similar to its Australian counterpart by not treating the term fair and reasonable as a composite term. This current approach which treats the term fair and reasonable disjunctively has raised concern especially where the adviser concludes that the offer is “not fair” but “reasonable.” This paper examines the current approach which the advisers must adopt in preparation of the advice circular. It explains the possible issues this new approach may encounter. References are made to the Australian experience and literature in dealing with preparation of the independent advice circular. An empirical study must be conducted in Malaysia in order to determine whether the current approach has indeed improved the quality of the advice circular